Genetic and epi-genetic alterations of the PTEN gene : key in the relationship between type 2 diabetes and cancer - Ayala Schimpf, Alan Rolando (2021)
Fil: Ayala Schimpf, Alan Rolando. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Instituto de Biotecnología Misiones “Dra. María Ebe Reca”. Laboratorio de Biotecnología Molecular; Argentina.